Factors involved in choosing a contraceptive method in adolescents in a health center from Huancavelica, 2021 - Quispe Castro, Paola Cecilia (2022)
The objective of the research work was: To determine the factors related to the choice of a contraceptive method in adolescents treated at Paucará health center from Acobamba, Huancavelica 2021. Methodology: The study was observational, analytical, relational level and of cross-section; The population was 250 adolescents and the sample was 103 adolescents treated in the obstetric service at Paucará Health Center. A valid and reliable questionnaire was used, then they were processed in the IBM SPSS version 25 statistical program. Results: Of the total of adolescents interviewed, 38.8% use a contraceptive method and 61.2% do not use it. 24.3% use a quarterly ampoule, 6.8% implants, 4.9% condoms and 1.9% Pill. Conclusion: The factors marital status, origin, occupation, having children, partner influence, free contraceptive methods (CM), history of CM use, information received at the health center and good treatment of health personnel, are related to the use of the contraceptive method. The P value found in all the mentioned factors were less than 0.05, so it is assumed that there is dependence between the mentioned factors and the use of a MAC.